A content analysis of the lyrics of Pinoy rock compositions from 1972 to March, 1981 - Arceo, Ma. Victoria D.
This study is a content analysis of 50 Pinoy Rock songs released from 1972 to March, 1981 with respect to different languages, themes, values, and interpersonal relationships that they contain and promote. It also used two sampling schemes with regards to the choice of sample. Out of a total of 183 Pinoy rock compositions, 50 songs and 25 replacements were taken using the simple random and systematic random sampling schemes.